2007
DOI: 10.1017/s1355770x07003920
|View full text |Cite
|
Sign up to set email alerts
|

Public disclosure of industrial pollution: the PROPER approach for Indonesia?

Abstract: This paper evaluates the effectiveness of the Program for Pollution Control Evaluation and Rating (PROPER) in Indonesia. PROPER, the first major public disclosure program in the developing world, was launched in June 1995; though it collapsed in 1998 with the Asian financial crisis, it is currently being revived. There have been claims of success for this pioneering scheme, yet little formal analysis has been undertaken. We analyze changes in emissions concentrations (mg/L) using panel data techniques with pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 19 publications
5
52
0
1
Order By: Relevance
“…This result comports with statistical and anecdotal evaluations of similar disclosure programs (Dasgupta et al 2007;García et al 2007García et al , 2009. We also find that plants in wealthier communities were more responsive to GRP ratings, as were single-plant firms.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result comports with statistical and anecdotal evaluations of similar disclosure programs (Dasgupta et al 2007;García et al 2007García et al , 2009. We also find that plants in wealthier communities were more responsive to GRP ratings, as were single-plant firms.…”
Section: Introductionsupporting
confidence: 85%
“…Of these papers, to our knowledge, only two- García et al (2007García et al ( , 2009)-present rigorous statistical analyses. Using panel data on both participants and nonparticipants, the authors find that Indonesia's PROPER spurred significant emissions reductions in wastewater discharges, particularly among plants with poor compliance records.…”
Section: Does Public Disclosure Improve Environmental Performance?mentioning
confidence: 99%
“…Toxic Release Inventory, arguably the best-known public disclosure program, is mixed (Bui 2005;Greenstone 2003;Koehler and Spengler 2007), studies of other programs have generated compelling evidence that public disclosure can drive emissions reductions. These programs include so-called performance evaluations and ratings initiatives in Indonesia and India (García et al 2007;Powers et al 2008); 1996 amendments to the U.S. Safe Drinking Water Act mandating that community drinking water systems publicly report regulatory violations (Bennear and Olmstead 2007); rules requiring U.S. electric utilities to publicly report the extent of their reliance on fossil fuels (Delmas, Montes-Sancho, and Shimshack 2007); and British Columbia's policy of publicizing the identity of plants that are noncompliant (Foulon, Lanoie, and Laplante 2002).…”
Section: Public Disclosurementioning
confidence: 99%
“…Afsah, Blackman, Garcia, & Sterner 2013 for detailed discussions about the scheme). A study of the scheme's effects in Indonesia found that the use of performance rating and the public disclosure of information about firms' compliance have led to a significant reduction in the costs of compliance assurance strategies (Garcia, Afsah, & Sterner, 2009;Garcia, Sterner, & Afsah, 2007). In Ghana, like Indonesia, the scheme works outside the formal court system and rather capitalizes on reputational incentives.…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, like Indonesia, the scheme works outside the formal court system and rather capitalizes on reputational incentives. Moreover, studies have shown that the power of ignominy could outweigh the gain from violation, and a significant number of firms improved their ratings within short periods of time when the scheme was introduced in Indonesia and Ghana (Afsah, et al, 2013;Garcia et al, 2007;Garcia et al, 2009). A pilot scheme was also introduced in Jiangsu Province, China, from 2005 to 2007 and the results were positive (Zhang, 2010).…”
Section: Introductionmentioning
confidence: 99%